CURRENT COMMENT. (America Magazine: The Jesuit Review of Faith & Culture, 1978)
This section offers U.S. news briefs as of June 10, 1978. The Archdiocese of Baltimore has asked the assistance of volunteer professionals in research, data processing and management studies in its step for modernization. U.S. Energy Secretary James M. Schlesinger said that the agreement of the U.S. Senate and House signify the end of dispute over the regulation of natural gas prices. The campaign for human rights by the administration of U.S. President Jimmy Carter was criticized because it allegedly threatens the treaty on strategic weapons.